Post-effort chances in C-reactive protein level among soccer players at the end of the training season - Kostrzewa-Nowak, D.; Nowak, R.; Chamera, T.; Buryta, R.; Moska, W.; Cieszczyk, P. (The Journal of Strength and Conditioning Research, 2015)
Numerous literature data point out the differences in immunological parameters as a result of physical effort and the relation of those changes to the subject's fitness level. This study was aimed at the assessment of soccer players' condition and adaptation to physical effort based on the changes in C-reactive protein (CRP) blood level. C-reactive protein, total protein, and albumin plasma levels before and after 60-minute-long outdoor running were determined among 16 (8 men and 8 women) soccer players. Statistically significant increase in total blood protein level was observed in both studied groups. However, there were no statistically significant changes in albumin level in soccer players' blood. Determination of CRP showed that the exercise test caused changes in its level among both women and men; yet, statistically significant increase in CRP level was found only in women's blood. The different influence of effort on CRP plasma level may be explained by the involvement of various mechanisms in regulation of acute-phase responses in different conditions. It was found in our study that CRP level could be a valuable tool to assess the metabolic response to aerobic exercise.